Etnicidad, política y medios de comunicación. Los rankülches de la provincia de San Luis, Argentina. - GIACOMASSO, María Vanesa (Chasqui (13901079), 2017)
This paper aims to analyze the visibilization of the indigenous people rankülche of San Luis (Argentina) in the press, in a context characterized by the implementation of actions by the provincial government during the 21st century. This is the restitution of land in 2007 and the construction of "Pueblo Ranquel" for the community life of this population, inaugurated in 2009. The objective is to examine the journalistic notes, paying special attention to the representations built towards the natives, as well as around the emerging relation between them and the state. The focus is set on news of El Diario de la República, at the province capital, although also includes publications of other national newspapers.